Cluster of invasive Mycobacteria chimaera infections following cardiac surgery demonstrating novel clinical features and risks of aortic valve replacement. Issue 12 (5th December 2018) - Overton, Kristen; Mennon, Vidthyia; Mothobi, Nomvuyo; Neild, Blake; Martinez, Elena; Masters, Jeffrey; Grant, Peter; Akhunji, Zakir; Su, Wei‐Yuen; Torda, Adrienne; Whyte, Claudia M.; Lloyd, Andrew; et al.
Abstract: There is a global outbreak of infections due to Mycobacterium chimaera associated with cardiac surgery. The most serious infections involve prosthetic material implantation, and all have followed surgical procedures involving cardiopulmonary bypass. We describe a cluster of four cases following cardiac surgery at a tertiary referral centre in Sydney, Australia. We report novel clinical findings, including haemolysis and kidney rupture possibly related to immune reconstitution inflammatory syndrome. The positive effect of corticosteroids on haemodynamic function in two cases and the failure of currently recommended antimicrobial therapy to sterilise prosthetic valve material in the absence of surgery despite months of treatment are also critically examined. Positron emission tomography was positive in two cases despite normal transoesophageal echocardiograms. The proportion of cases with M. chimaera infection after aortic valve replacement (4/890, 0.45%; 95% confidence interval 0.18–1.15%) was significantly higher than after all other cardiothoracic surgical procedures (0/2433, 0%; 95% confidence interval 0–0.16%).